The impact of drought length and intensity on N cycling gene abundance, transcription and the size of an N2O hot moment from a temperate grassland soil. (May 2022) - Barrat, H.A.; Clark, I.M.; Evans, J.; Chadwick, D.R.; Cardenas, L.
Abstract: This study aimed to investigate the relationship between drought length, drought intensity and the size of the N2 O hot moment. It selected two treatments to deduce the main nitrogen cycling process producing N2 O (increasing WFPS from 40% to 90%, and from 70% to 90%), by destructively sampling soil cores to analyse gene abundance, transcription, and changes in soil chemistry (TON, NH4 +, DOC). Five other drought and rewetting treatments on packed soil cores were selected to create the drought curves described in Barrat et al. (2020) : these included increases of WFPS from 40% to 90%, 50%–90%, 60%–90%, 70%–90%, and 30%–60%. For each treatment, drought lengths were imposed from 0 to 30 days. A quadratic linear regression was fitted to the cumulative emissions data. This model explained a significant proportion of the total variation in the data (R 2  = 0.72, p ≤ 0.001). All treatments had an increase in daily N2 O emissions post wetting typical of a hot moment apart from the 30%–60% WFPS treatment. In terms of drought intensity, the 40%–90% WFPS was significantly larger than rest, probably due to a relatively larger change in water potential compared to the other treatments. The response to drought length followed a quadratic curve with a downward linear trend, with the largest emissions observed between 10 and 15 days of drought, and the smallest at 0 and 30 days. We suggest a 2-stage dormancy strategy to explain this, where microbes under dry conditions store osmolytes which are catabolised upon rewetting, however at prolonged negative water potentials this strategy is no longer effective, and so they enter a deeper state of dormancy where they can no longer rapidly respond to the changing water potential. Given the delayed response after rewetting, and the inverted U shaped curve in terms of drought length, it seems likely that the majority of emissions are of biological origin. The soil's chemistry data suggested that NH4 + was a key factor controlling the emission flux, but the transcriptional and genomic data were inconclusive. This study therefore suggests that future experiments should focus changes in osmolyte accumulation and catabolism as the key explanation for N2 O hot moments, rather than changes in genomic and transcriptomic data or soil substrates, which do not always correlate with emissions. Highlights: A greater drying intensity results in larger N2 O emissions if soil is sufficiently rewetted. Drought length and the size of N2 O hot moments are negatively related and non-linear. We observed no significant differences in transcription activity for N cycling genes. We suggest a two step drought response to explain differences in N2 O emissions.